(untitled) (Bangladesh Journal of Agricultural Research, 2019)
The experiment was conducted with 61germplasm of blackgram (Vigna mungo (L.) Hepper) in a Randomized Complete Block Design with 3 replications at the Plant Genetic Resources Centre of BARI Gazipur during March to June 2012 to know the diversity of germplasm. Two to four classes were observed among the 14 qualitative characters. Green and purple colours were found in epicotyl, petiole and stem. Light green to dark green was found in case of leaf and immature pods. Erect, semi-erect and spreading growth habit along with indeterminate and determinate growth pattern were observed. Ovate, ovate-lanceolate and rhombic terminal leaflet shape were found. Erect to sub-erect pod attachment to peduncle with glabrous to densely pubescent pods were found. The accessions showed black and brown mature pods having hook and knob types of pod beak shape. Black, brown, grayed-orange and yellow-green seed colours were observed among the blackgram accessions. Low to high phenotypic diversity index (0.12 to 0.91) were found among the qualitative characters. All the accessions exhibited purple hypocotyl, none twining tendency, glabrous leaf pubescence, abundant leafiness, very light green calyx, yellow flower, drum-shaped seeds, absent seed luster and non-concave seed hilum. Number of seeds per pod ranged from 5 to 7 and hundred seed weight ranged from 1.83 to 4.49 g. The highest PCV was observed in branch length (32.65%) and the lowest PCV was found in pod length (6.99%). The accessions were grouped into five clusters. Accessions collected from the same districts felt into different clusters. The inter and intra cluster distances ranged from 3.37 to 11.38 and 0.30 to 1.17, respectively. The maximum number of pods per plant, pod length and 100-seed weight was found in cluster IV. Accessions BD-6853, BD-6857, BD-6863, BD-6865 and BD-6866 were identified as potential germplasm for varietal improvement programme. Bangladesh J. Agril. Res. 44(2): 239-251, June 2019